Systematic analysis of MADS-box gene family in the U’s triangle species and targeted mutagenesis of BnaAG homologs to explore its role in floral organ identity in Brassica napus - Song, Min; Zhang, Yanfeng; Jia, Qingli; Huang, Shuhua; An, Ran; Chen, Nana; Zhu, Yantao; Mu, Jianxin; Hu, Shengwu (Frontiers in Plant Science, 2023)
MADS-box transcription factors play an important role in regulating floral organ development and participate in environmental responses. To date, the MADS-box gene family has been widely identified in Brassica rapa (B. rapa), Brassica oleracea (B. oleracea), and Brassica napus (B. napus); however, there are no analogous reports in Brassica nigra (B. nigra), Brassica juncea (B. juncea), and Brassica carinata (B. carinata). In this study, a whole-genome survey of the MADS-box gene family was performed for the first time in the triangle of U species, and a total of 1430 MADS-box genes were identified. Based on the phylogenetic relationship and classification of MADS-box genes in Arabidopsis thaliana (A. thaliana), 1430 MADS-box genes were categorized as M-type subfamily (627 genes), further divided into Mα, Mβ, Mγ, and Mδ subclades, and MIKC-type subfamily (803 genes), further classified into 35 subclades. Gene structure and conserved protein motifs of MIKC-type MADS-box exhibit diversity and specificity among different subclades. Comparative analysis of gene duplication events and syngenic gene pairs among different species indicated that polyploidy is beneficial for MIKC-type gene expansion. Analysis of transcriptome data within diverse tissues and stresses in B. napus showed tissue-specific expression of MIKC-type genes and a broad response to various abiotic stresses, particularly dehydration stress. In addition, four representative floral organ mutants (wtl, feml, aglf-2, and aglf-1) in the T0 generation were generated by editing four AGAMOUS (BnaAG) homoeologs in B. napus that enriched the floral organ variant phenotype. In brief, this study provides useful information for investigating the function of MADS-box genes and contributes to revealing the regulatory mechanisms of floral organ development in the genetic improvement of new varieties.